The Exploitation of Women's Body and Sensuality: The Attraction of Newspaper Movie Advertisements in The Local Daily Newspapers (Waspada, Sinar Indonesia Baru, and Analisa) in Medan in the 1970s - Hati, Lila Pelita; Ginting, Lestari Dara Cinta Utami; Malik, Rahman (Tradition and Modernity of Humanity, 2022)
Newspaper advertising experienced a significant increase in the 1970s. During that period, three local daily newspapers were established in Medan: Waspada, Sinar Indonesia Baru, and Analisa. These newspapers displayed various advertisements in their publications, one of which was the advertisement to promote the film that would be shown in theaters at that time. In promoting films through these advertisements, many producers use women as a means of promotion. Women have their magnet to attract the audience's interest. This journal explains how women’s representation in the local daily newspaper advertisements in Medan in the 1970s and how the exploitation of women’s bodies and sexual attractiveness in the advertisements for the film's promotion was related to global discourse, especially in terms of women's appearance. The four stages of historical methods are applied to conduct the research: heuristics, verification, interpretation, and historiography. The research results show that advertising producers often showcased pictures of beautiful and sexy women and even displayed vulgar words to attract the audience's interest which didn't represent the storyline of the film itself.